Comparison of the Effectiveness of Dialectical Behavior Therapy and Cognitive-Behavioral Therapy on the level of Attention in Girl students with Obsessive-Compulsive Disorder - Haleh Amighi; Hossein Ebrahimi Moghadam; Leila Kashani Vahid (مجله علوم پزشکی صدرا, 2025)
Introduction: Adolescent Obsessive-compulsive disorder includes all disturbing thoughts that, in the worst possible case, involve them (especially girls) repeatedly. The present study aimed to compare the impact of dialectical behavior therapy (DBT) and cognitive-behavioral therapy (CBT) on attention in patients with obsessive-compulsive disorder (OCD).Methods: In this quasi-experimental research, employing a pretest-posttest-follow up (2 months) control group design, the study population comprised girls diagnosed with OCD from the first and second level secondary schools in districts 1 and 3 of Tehran, Iran, during 2022. Through convenience sampling, a total of 45 (15 people in each group) participants were randomly selected and allocated to the experimental and control groups. In order to collect data, the Maudsley’s Obsessive Compulsive Inventory (1977) and the Rosvold’s Continuous Performance Test (1956) were employed. The CBT and DBT (8 sessions of 90 minutes each) were administered to experimental groups 1 and 2, respectively. The analysis of the collected data was conducted using SPSS22, employing the method of multivariate mixed analysis of variance.Findings: The results showed that both methods CBT and DBT improved subscales of omission error (MD=-8.112, -8.252), commission error (MD=-1.269, -2.6), reaction time (MD=-17.227, -11.256) in girls with OCD when compared to the control group (P<0.05). Moreover, it was found that the method of CBT works better than DBT in the case of commission errors, but this result is the opposite in the reaction time.Conclusion: Considering the psychological vulnerability of obsessive-compulsive girls, CBT and DBT packages can be used to improve their psychological level.